Implementation of Hypovolemia Management with Hypovolemia Nursing Problems in Open Fracture Patients - Rosita, Leni; Hibahtulloh, Arif (Althar Cendikia Education, 2024)
Fracture is a disruption of bone continuity that causes tissue and blood vessel damage, resulting in bleeding around the fracture and soft tissue, which can cause hypovolemia. The most effective way to overcome this problem is with hypovolemia management. The purpose of this study was to determine the application of hypovolemia management in open fracture patients who experience hypovolemia. The method used in this compilation is a descriptive type of compilation. Qualitative compilation is a compilation of research that is descriptive in nature and tends to use analysis with the study subjects in this case being 2 patients who experienced open fracture health problems with hypovolemia nursing problems with patient criteria: Patients with open fractures, experiencing hypovolemia nursing problems, and willing to undergo hypovolemia management. Data collection according to the assessment format, focused on subjective and objective data to facilitate data collection regarding the application of hypovolemia management in fracture patients. The diagnosis made was hypovolemia related to active fluid loss, with hypovolemia management intervention. The conclusion of the case study showed that the condition of the two patients began to improve after hypovolemia management was carried out.